VIRTUAL PUBLIC SPHERES IN LITHUANIA: THE POLITICIZING EFFECT OF THE INTERNET - Vinogradnaitė, Inga (Politologija, 2015)
There is an agreement among political scholars that political conversation is a good thing and a necessary condition of a viable democracy. Political conversations are said to make individuals better informed, with enlarged understanding and opinion and a sense of efficacy which is necessary to get involved into political activities. Yet, political talk, due to its potential to arouse disagreement and dispute, is something what most people tend to avoid in order to preserve their social ties. On the other hand, political talk which would be less disruptive if taking place among mere acquaintances is rare as people tend to spend their leisure in private instead of gathering together in public spaces. Internet seems to offer a possible solution in such situation. It does not require leaving home and yet makes it possible to meet other people. The aim of this article is to explore the politicizing effects of the Internet on social networks. The term “politicized social network” refers to the networks with the following property: their ties serve as channels to communication political information, opinions and support. In other words, individual is described as possessing politicized social networks if he engages regularly in political conversations with his relatives, friends or acquaintances.Politicizing effects may be defined both in quantitative and qualitative terms. First, politicization of social networks means enlargement of number of ties with individuals with whom one often talks politics. Second, politicization of social networks means exposure of individuals to new experiences of political talk. Assuming that most of the ordinary conversations are homogenous, that is, taking place among individuals who held the same opinions or at least are not willing to argue and to express disagreement, the essence of politicizing effects of the Internet lies in its possibilities to expose people to “cross-cutting” political conversations. This potential of the Internet, however, depends not only on the characteristics of the medium, but also on the motivation of its consumers. In order to explore both quantitative and qualitative aspects of the politicizing potential of the Internet, the data of a representative survey of Lithuanian population is analyzed. The results of analysis show that effects of the Internet on politicization of social networks, if assessed in quantitative terms, are rather limited with the notable exception of younger parts of population. On the other hand, these effects might acquire a higher significance if one takes into account their qualitative aspect. Though it is sometimes feared that the possibilities to filter political information might tempt individuals to limit their communication only with the like-minded people, the results show that such predictions rest on a false assumption concerning the motivations, which lead individuals to engage into virtual political discussions. Therefore, however limited in quantitative terms, the effect of the Internet on social networks is important in terms of its potential to bring the experiences of diversity and “cross-cutting” conversation.